SIFAT SUI GENERIS PERJANJIAN PEMANFAATAN TANAH INDUSTRI ATAS TANAH HAK PENGELOLAAN BADAN USAHA MILIK NEGARA - Arif Budi Santoso; Hwian Christianto (LPPM STIH Awang Long, 2026)
This article examines the juridical character of Industrial Land Utilization Agreements (Perjanjian Pemanfaatan Tanah Industri/PPTI) that give rise to Building Use Rights (Hak Guna Bangunan/HGB) over Management Rights (Hak Pengelolaan/HPL) held by State-Owned Enterprises (BUMN) managing industrial estates. The central problem lies in the legal classification of PPTI, which is often understood in practice as either a sale and purchase transaction or a lease agreement. Using normative legal research with statutory, conceptual, limited case-based, and comparative approaches, this article analyzes the relationship between state control over land, HPL authority, contractual obligations, HGB as a land right, and legal certainty. The findings show that PPTI cannot be reduced to a conventional sale and purchase because HPL is not transferred to investors. It also cannot be treated as a pure lease because PPTI becomes the basis for the issuance of HGB, which has administrative and proprietary effects and may serve as collateral under certain legal requirements. Therefore, PPTI is more appropriately qualified as a sui generis agreement: a special contractual construction that combines public authority, private contractual relations, land administration, and property-law consequences. This classification contributes to legal certainty by clarifying the position of BUMN as HPL holders, investors as HGB holders, creditors as security holders, and public authorities in interpreting industrial land utilization consistently.